PENGARUH PERSONAL SELLING DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK KECANTIKAN PURBASARI SAGA DEPARTEMEN STORE KOTA SORONG - Susetyowati Sofia; Miranty; Agilistya Rahayu (KALIANDA HALOK GAGAS, 2023)
ABSTRACT : This study aims to determine whether personal selling and product quality have an effect on purchasing decisions at Purbasari Saga Outlets, Sorong City Dept. Store. This study uses descriptive quantitative research methods and correlations. The data collection technique is by distributing online and offline questionnaires to 75 respondents who are Outlet Customers of Purbasari Saga Dept.Store, with a population of 93 people and a sample of 75 people derived from the slovin formula. The data analysis method used multiple linear regression analysis and hypothesis testing (t-test, f-test and coefficient of determination test). Researchers tested primary data in this study using the SPSS version 20 application program for windows and secondary data. The results of the multiple linear regression analysis that have been carried out using the SPSS version 20 application program for windows, the results obtained are Y=2.465+0.156X_1+0.062X_2